PKD2 Functions as an Epidermal Growth Factor-Activated Plasma Membrane Channel - Ma, Rong (American Society for Microbiology, 2005)
PKD2, or polycystin 2, the product of the gene mutated in type 2 autosomal dominant polycystic kidney disease, belongs to the transient receptor potential channel superfamily and has been shown to function as a nonselective cation channel in the plasma membrane. However, the mechanism of PKD2 activation remains elusive. We show that PKD2 overexpression increases epidermal growth factor (EGF)-induced inward currents in LLC-PK(1) kidney epithelial cells, while the knockdown of endogenous PKD2 by RNA interference or the expression of a pathogenic missense variant, PKD2-D511V, blunts the EGF-induced response. Pharmacological experiments indicate that the EGF-induced activation of PKD2 occurs independently of store depletion but requires the activity of phospholipase C (PLC) and phosphoinositide 3-kinase (PI3K). Pipette infusion of purified phosphatidylinositol-4,5-bisphosphate (PIP(2)) suppresses the PKD2-mediated effect on EGF-induced conductance, while pipette infusion of phosphatidylinositol-3,4,5-trisphosphate (PIP(3)) does not have any effect on this conductance. Overexpression of type Iα phosphatidylinositol-4-phosphate 5-kinase [PIP(5)Kα], which catalyzes the formation of PIP(2), suppresses EGF-induced currents. Biochemical experiments show that PKD2 physically interacts with PLC-γ2 and EGF receptor (EGFR) in transfected HEK293T cells and colocalizes with EGFR and PIP(2) in the primary cilium of LLC-PK(1) cells. We propose that plasma membrane PKD2 is under negative regulation by PIP(2). EGF may reduce the threshold of PKD2 activation by mechanical and other stimuli by releasing it from PIP(2)-mediated inhibition.